Atorvastatin Treatment of Cavernous Angiomas with Symptomatic Hemorrhage Exploratory Proof of Concept (AT CASH EPOC) Trial. Issue 6 (26th November 2018) - Polster, Sean P; Stadnik, Agnieszka; Akers, Amy L; Cao, Ying; Christoforidis, Gregory A; Fam, Maged D; Flemming, Kelly D; Girard, Romuald; Hobson, Nicholas; Koenig, James I; Koskimäki, Janne; Lane, Karen; et al.
Abstract: BACKGROUND: More than a million Americans harbor a cerebral cavernous angioma (CA), and those who suffer a prior symptomatic hemorrhage have an exceptionally high rebleeding risk. Preclinical studies show that atorvastatin blunts CA lesion development and hemorrhage through inhibiting RhoA kinase (ROCK), suggesting it may confer a therapeutic benefit. OBJECTIVE: To evaluate whether atorvastatin produces a difference compared to placebo in lesional iron deposition as assessed by quantitative susceptibility mapping (QSM) on magnetic resonance imaging in CAs that have demonstrated a symptomatic hemorrhage in the prior year. Secondary aims shall assess effects on vascular permeability, ROCK activity in peripheral leukocytes, signal effects on clinical outcomes, adverse events, and prespecified subgroups. METHODS: The phase I/IIa placebo-controlled, double-blinded, single-site clinical trial aims to enroll 80 subjects randomized 1-1 to atorvastatin (starting dose 80 mg PO daily) or placebo. Dosing shall continue for 24-mo or until reaching a safety endpoint. EXPECTED OUTCOMES: The trial is powered to detect an absolute difference of 20% in the mean percent change in lesional QSM per year (2-tailed, power 0.9, alpha 0.05). A decrease in QSM change would be a signal of potential benefit, and an increase would signal a safety concern with the drug. DISCUSSION: With firm mechanistic rationale, rigorous preclinical discoveries, and biomarker validations, the trial shall explore a proof of concept effect of a widely used repurposed drug in stabilizing CAs after a symptomatic hemorrhage. This will be the first clinical trial of a drug aimed at altering rebleeding in CA.